Analysis of Factors Influencing the Demand for Money in Indonesia for the Period 2010Q1-2024Q4 - Mita Apriani; Ida Ayu Putri Suprapti (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
M2 money demand in Indonesia is influenced by crucial macroeconomic factors such as real GDP, inflation, BI Rate, and economic uncertainty, but their effects are not empirically consistent. This study aims to analyze the influence of these variables on M2 money demand for the 2010Q1-2024Q4 period. Using a quantitative approach with secondary quarterly time series data from BPS, BI, and FRED (60 observations), the analysis was conducted through the Error Correction Model (ECM) in EViews 10 including the ADF test, OLS, Engle-Granger cointegration, and classical assumption tests. The results show that real GDP has a significant positive effect in both the long term (β = 2.153708; p = 0.0000) and short term (γ = 0.287925; p = 0.0361), while inflation, interest rates, and the uncertainty index are insignificant. ECT = -0.151084 (p = 0.0084) indicates an adjustment of 15.11% per period. The study concludes that GDP is the main driver of M2 with implications for monetary policy focusing on economic growth.